2008
DOI: 10.2341/07-145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Double-application or the Application of a Hydrophobic Layer for Improved Efficacy of One-step Self-etch Systems in Enamel and Dentin

Abstract: The effects of using the double-application and placement of a hydrophobic resin coat on microtensile dentin-bond strength values seem to be effective; however, these techniques in enamel were adhesive-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 22 publications
3
54
1
10
Order By: Relevance
“…5,7,8,10,16 To overcome this early degradation, some investigations have revealed that the application of more hydrophobic resins over hybridized tissues provides better sealing of acid-etched dentin 9,18-21 and higher bond strength of composite to dentin. 19,20,22 In this study, the use of flowable resin or an additional layer of more hydrophobic adhesive did not improve the percentage dentin sealing of any type of adhesive.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5,7,8,10,16 To overcome this early degradation, some investigations have revealed that the application of more hydrophobic resins over hybridized tissues provides better sealing of acid-etched dentin 9,18-21 and higher bond strength of composite to dentin. 19,20,22 In this study, the use of flowable resin or an additional layer of more hydrophobic adhesive did not improve the percentage dentin sealing of any type of adhesive.…”
Section: Discussionmentioning
confidence: 94%
“…16,17 To improve the sealing ability of one-step self-etching adhesives, some authors have suggested the application of an additional layer of hydrophobic material in an attempt to reduce the concentration of hydrophilic monomers to be light cured. 9,[18][19][20][21][22] The importance of studying dentin permeability in relation to the sealing ability of adhesive systems is that, besides bonding the restorative material to the tooth, adhesive systems are responsible for sealing the resin-dentin interface against microleakage and avoiding restorative material debonding, which could compromise the restorations. 2,16,17 The objective of this study was to measure fluid flow through the adhesive-dentin interfaces created by eight bonding agents using a permeability device.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…147 To counteract this limitation of simplified adhesives, it has been proposed that the application of an additional layer of hydrophobic fluid resin should be incorporated to their bonding protocol. 24,148,149,150,151,152 This strategy proved to be effective in minimizing nanoleakage and improving the polymerization of simplified adhesives 150 as well as their immediate 40,146,150 and long-term 146 bond strength. It could also improve the sealing ability of two-step etch-and-rinse adhesives by reducing fluid conductance across the adhesive interface.…”
Section: Addition Of a Separate Hydrophobic Adhesive Resinmentioning
confidence: 99%
“…The latest generation all-in-one adhesive have combined these steps into a single-step application for simpler and faster application [3][4][5][6]. All-in-one adhesive are mixtures of hydrophobic and hydrophilic monomers and solvents, combining etching, priming and bonding into a single product [3,[7][8][9]. They are mixed together immediately before use and then applied to tooth substrate and some of them were presented as a mixture of these adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Applying an additional adhesive layer can increase acidic monomer concentration and this may lead to improve the demineralization effect, hybrid layer quality and better micromechanical bonding [4,8,10,14].…”
mentioning
confidence: 99%